P-31 Preparing for the evaluation of an enhanced community palliative support service (encompass). Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Fitzsimmons, Deborah; Ariss, Steven; Mawson, Susan
Abstract : Research aims: To document and analyse current operating practices for community palliative care services prior to the introduction of new technologies and changed working practices. Background: In line with national priorities, one UK hospice is introducing new technologies to support the redesign of their community services; improve patient experience; and expand service provision. Rather than the existing model of 1:1 community-based nursing by senior specialist nurses, junior nurses will be delegated to deliver palliative care plans under online supervision by specialist palliative care nurses. The technologies provide online access to up-to-date clinical records to support effective team interaction and decision-making, enable point-of-care documenting of observations and care delivery, and immediate access to support from specialist clinicians. This initial study has benchmarked existing community palliative care delivery in preparation for the subsequent operational and financial evaluation of the new service and has: Identified and documented current working practices; Identified and isolated the key costs and benefits of the service; Established current data input and data use; and Assessed current patient outcomes. Methods: A mixed methods approach was used to understand a wide range of organisational, economic, and patient-level factors; examine the barriers to, and facilitators of, the implementation of this innovative service modeland explain how and why specific changes are expected to occur. Data has been collected using interviews, focus groups, observation, routinely collected data and documents. Results: This presentation will report on the study, including development of an organisational model incorporating proposed changes from the introduction of new technologies. This model will guide the gathering and analysis of evidence to describe the actual changes achieved and explain any differences between these and the anticipated model. Conclusions: Developing and evidencing improved efficiency in community-based services poses a number of challenges for providers, requiring significant changes to current practice, together with technology-based enablers.